The posttraumatic cognitive appraisal inventory (PTCAI): development and validation - Zhang, Wenyue; Yu, Wenjing; Wei, Baojian; Dong, Qianni; Zhang, Aihua (Frontiers in Psychology, 2023)
Objective: This study aims to develop and validate the Posttraumatic Cognitive Appraisal Inventory (PTCAI) for accidental trauma survivors.Method: Based on interviews and expert feedback, the initial item pool was generated for the negative cognitive appraisal subscale of Loss and Feeling Threatened, and the positive cognitive appraisal subscale of Positively Face, Self-Sense, and Relationships. Then, we recruited two groups of accidental trauma survivors to examine the reliability and validity of the PTCAI. Item analysis and exploratory factor analysis (EFA) were conducted on Sample 1. Confirmatory factor analysis (CFA), Pearson correlation analysis, and internal consistency reliability analysis were applied to Sample 2.After two weeks, 20 survivors completed the PTCAI again to test temporal stability.Results: Following item analysis, the PTCAI was reduced to 27 items. The results of the EFA demonstrated that the five-factor, 27-item solution of the PTCAI was appropriate, which accounted for 63.931% of the total variation. The CFA indicated that the five-factor second-order model offered an excellent fit to the data. Loss and Feeling threatened were equally important in the study participants' negative cognitive appraisal of accidental traumas. Self-sence was the most important positive cognitive appraisal of accidental traumas by the study participants. Positively Face and Relationships were somewhat behind. Additionally, the PTCAI demonstrated high concurrent validity and reliability (test-retest and internal consistency).The PTCAI appears to be a reliable and valid instrument for assessing cognitive appraisals of accidental trauma survivors.